2012
DOI: 10.1002/ajpa.22184
|View full text |Cite
|
Sign up to set email alerts
|

The ranging behavior of Lemur catta in the region of Cap Sainte‐Marie, Madagascar

Abstract: Large home ranges and extreme flexibility in ranging behaviors characterize most subarid dwelling haplorhines. However, the most comparable extant strepsirhine, Lemur catta, is characterized as having small home ranges with consistent boundaries. Since ranging studies on this species have been limited to gallery forest habitat, the author's goal is to identify ecological factors that affect range use of L. catta in one of the most resource-limited environments of its distribution. To conduct this study, rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(49 citation statements)
references
References 72 publications
0
49
0
Order By: Relevance
“…L. catta is an ecologically flexible species Gould, 2006); however, it can be highly sensitive to habitat disturbance, with populations occurring at much lower densities in habitats of poorer quality Kelley, 2013;Gould & Andrianomena, 2015;Gould & Sauther, 2016;LaFleur et al, 2017). Due to the rapid loss of continuous habitat throughout its range in recent decades Bodin et al, 2006;Goodman, Rakotoarisoa & Wilme, 2006;Brinkmann et al, 2014;Gould & Sauther, 2016;LaFleur et al, 2017), L. catta has become a flagship species for conservation in Madagascar.…”
Section: Introductionmentioning
confidence: 99%
“…L. catta is an ecologically flexible species Gould, 2006); however, it can be highly sensitive to habitat disturbance, with populations occurring at much lower densities in habitats of poorer quality Kelley, 2013;Gould & Andrianomena, 2015;Gould & Sauther, 2016;LaFleur et al, 2017). Due to the rapid loss of continuous habitat throughout its range in recent decades Bodin et al, 2006;Goodman, Rakotoarisoa & Wilme, 2006;Brinkmann et al, 2014;Gould & Sauther, 2016;LaFleur et al, 2017), L. catta has become a flagship species for conservation in Madagascar.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from other non-gallery forest sites report large ring-tailed lemur group sizes without accompanying increases in Tamarindus density. Group sizes of >15 individuals (adults and subadults) inhabit the mixed deciduous/spiny bush forest of Tsimanampesotse National Park where Tamarindus has a limited distribution [LaFleur et al, 2014], and groups of 11-15 individuals occur in the far south in Cap Sainte-Marie where there is no tamarind [Kelley, 2013]. We also observed other large groups of ring-tailed lemurs on top of the escarpment while following our primary study group.…”
Section: Discussionmentioning
confidence: 57%
“…The tamarind fruits in these forests constitute the major food item annually for the lemurs, yet Tamarindus may be an exotic species to Madagascar, and reliance on its fruit may be of recent origin [Sauther and Cuozzo, 2009]. More recent surveys and field studies of populations from high altitudes to spiny desert scrub have broadened our understanding of what constitutes 'normal' conditions for ring-tailed lemurs [Goodman and Langrand, 1996;Gould et al, 2011;Kelley, 2013;LaFleur et al, 2014]. These sites typically have little to no tamarind trees, yet support sizable ring-tailed lemur populations.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the habitat quality, the home range sizes of ring-tailed lemurs vary strongly in the wild (Sussman, 1991). In Madagascar's gallery forests they most commonly occupy home ranges from 6 to 30 ha (Sussman, 1991;Sauther et al, 1999;Mertl-Millhollen et al, 2003), while in drier habitats home ranges of up to 87-132 ha have been reported (Kelley, 2013). In richer habitats or during wet season, however, home ranges can also be as small as 2.6 ha (Gabriel, 2013).…”
Section: Discussionmentioning
confidence: 99%